Application of Spatial and Network Analysis to Evaluate Shelter Plan for Tsunami Evacuation - Sigit Sutikno; Keisuke Murakami (Institute of Research and Community Outreach - Petra Christian University, 2015)
This study proposes a method for evaluating shelter plan for emergency evacuation prior to a tsunami based on service area analysis. The evacuation service areas are generated using both spatial and network analysis based on Geographic Information System (GIS). A case study in Pacitan city, East Java Province, Indonesia which is located in the South coastal area of Java Island, is picked as study area. The field has a possibility of suffering tsunami disaster because of the movement of Indo-Australian plate and Eurasian plate. The simulation result shows that the current evacuation shelters arranged by local government are not easy to access if tsunami occurs. About 50% of the residents do not have enough time to evacuate to the shelters because many shelters are located far from residential area. Utilizing public buildings around residential area for temporary shelters proposed in this study, about 96% residents in inundation area have sufficient time to evacuate to the shelters.